Patient-centered collaborative care approach to medical-surgical nursing : volume 2 - Ignatavicius, Donna D.; Workman, M. Linda (Singapore : Saunders/Elsevier, 2010)
The sixth edition includes a new emphasis on clinical decision-making for patient-centered collaborative care and more streamlined and balanced coverage of the core body of knowledge needed for safe clinical practice. There is also expanded coverage of emergency and disaster preparedness along with an enhanced "Get Ready for the NCLEX Examination" feature that includes the addition of new NCLEX Challenge questions. --from publisher description
Rev. ed. of: Medical-surgical nursing : critical thinking for collaborative care. 5th ed. c2006. Includes index. Pagination 1070 - 1819 p.
NUR
Keywords: Surgical nursing; Perioperative nursing; Medical-Surgical nursing